2021
DOI: 10.1097/mpg.0000000000003058
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Improve Enteral Feeding Tolerance in Pediatric Short Bowel Syndrome With Chronic Intestinal Inflammation

Abstract: Objectives: A group of short bowel syndrome (SBS) patients developed chronic intestinal inflammation while struggling weaning off parenteral nutrition (PN). They did not respond to standard management of SBS and food allergy. We treated them with glucocorticoids and described the outcome. Methods: Our study is a retrospective descriptive study. We reviewed records from the intestinal rehabilitation program from 2006 to 2017. We identified 15 patients whose lab values, pathology results, and clinic notes were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although endoscopic assessments are used, consistent with grade show that anti-inflammatory therapy is especially important in the pathogenesis of SBBO and that there may be overlap with IBD in SBS patients 13,14 . Lastly, the study relied on clinical diagnosis of SBBO, which is not recommended in the adult literature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although endoscopic assessments are used, consistent with grade show that anti-inflammatory therapy is especially important in the pathogenesis of SBBO and that there may be overlap with IBD in SBS patients 13,14 . Lastly, the study relied on clinical diagnosis of SBBO, which is not recommended in the adult literature.…”
Section: Discussionmentioning
confidence: 92%
“…We furthermore did not assess resistant organism formation or prevalence of fungemia with respect to SBBO treatment. Current literature and future studies may show that anti‐inflammatory therapy is especially important in the pathogenesis of SBBO and that there may be overlap with IBD in SBS patients 13,14 . Lastly, the study relied on clinical diagnosis of SBBO, which is not recommended in the adult literature 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of glucocorticoids should be individualized in children with SBS-related chronic intestinal inflammation. One study reported that some pediatric patients with significant eosinophils in their intestinal biopsy responded well to glucocorticoids [15]. Thus systemic glucocorticoids can be useful for treating EGIDs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Nevertheless, with the short residence time in the intestine, the limited digestibility and absorbability in the intestine forces FNutF to combine with other drugs to treat SBS and undermines the long‐term benefit of this treatment clinically. [ 12 ] Therefore, the development of a new and pragmatic therapeutic strategy for SBS is warranted.…”
Section: Introductionmentioning
confidence: 99%